Magnetic-Mixed Convection in Nanofluid-Filled Cavity Containing Baffles and Rotating Hollow-Cylinders with Roughness Components. (14th December 2022) - Ali, Mohammad Mokaddes; Akhter, Rowsanara; Alim, Md. Abdul; Miah, Md. Musa
Abstract : Mixed convective heat transfer in a nanofluid-filled lid-driven square cavity equipped with a rotating cylinder, horizontal baffles, and an external magnetic field is numerically examined in this study. A cylinder with triangular components is set at the centre of the cavity while two horizontal baffles are fixed to its vertical walls. The cavity is under the impact of the external magnetic field. Modified Maxwell's model is taken into consideration to estimate the thermal conductivity of nanofluids. Galerkin FEM is applied to simulate nondimensional governing equations. The computations are carried out for specific ranges of physical parameters, and the results are illustrated through streamlines, isotherms, and average Nusselt number bar charts. Contours plotting indicate that flow circulation and distribution of temperature are significantly affected by the speed of a rotating rough cylinder. The fluid velocity remarkably increases with an increase in speed ratio and Reynolds number but it declines with Hartmann number, baffle length, and volume fraction. Heat transfer rate is substantially augmented by increasing the rotational speed of the rough cylinder, heights of triangular components, and suspended-nanoparticles which are also optimized for increasing baffle's length and its horizontal arrangement. The findings of this investigation can be applied to improve the cooling efficiency of engineering equipment such as heat exchangers, energy storage systems, electronic equipment, solar collectors, and nuclear reactor safety devices.